Female directors on board: the roadmap for India - Jaiswal, Anindita (The University of Edinburgh, 2020)
“One woman” to “one independent woman” director … where next? This statement explains the core of this thesis, which aims to craft a future roadmap for India in relation to boardroom gender diversity. In line with global trends seeking to promote women to corporate leadership positions, and concurrent with the overhaul of its company law, India enacted a “one woman director” quota for boardrooms in certain categories of public companies, including all listed ones. Enforced in 2013, and with a deadline of 2015, this would appear to be in line with legislation in countries such as Norway and France and in contrast to voluntary or softer measures adopted by some other countries such as the United Kingdom (UK) and Sweden. To assess India’s mandatory quota and suggest a future regulatory course, it is imperative to understand what causes such divergence in legal strategies across countries. Hence, this thesis commences with the question of why gender diversity is needed in boardrooms, particularly how this issue is seen from a country’s regulatory standpoint. This question is explored specifically in the jurisdictions of Norway and the UK, alongside a parallel review at pan-European Union level. Once the thesis identifies the rationale for each, it then explores the nexus between such rationales and the policy approaches or legal strategies adopted. This helps in explaining what determines their choice for a mandatory quota or discretionary targets – in other words, the connection between the reason why a country seeks female directorship and how it regulates or implements that. While offering this explanation, the thesis examines in greater detail the nuances of hard law versus soft law as policy approaches, specifically within the realm of corporate governance and boardroom gender diversity. Next, based on the connections deduced, this thesis makes an attempt to theorise (which is largely absent in the reviewed literature on the subject) how a legal strategy is derived, and, furthermore, how an optimum strategy can be formulated in this regard. It also makes a few proposals towards potential optimum strategies for such diversity. However, as much depends on the national context in which it is adopted and implemented, the focus then turns towards India. Starting with a review of India’s “one woman director” quota and its underlying rationale and justifications (inferred from scantily available sources), this thesis investigates how the quota has performed and its results, based on an in-depth and purposive study of 100 top and medium-sized listed (Nifty 50 and Nifty mid-cap 50) companies in India. The strategy (including the recently announced regulatory reform that requires a “one independent woman” quota), in light of these results, is then compared and mapped out with respect to India’s rationale to identify if they correlate. For the gaps or mismatches that exist, alongside the country-specific challenges (which appear to have been overlooked), this thesis then proposes an extensive regulatory roadmap. In addition to fixing such discrepancies, the aim is to offer more workable/optimum strategic solutions, which would provide an all-inclusive (involving both the regulator and the industry) way forward for India.
Keywords: law-making; policy approach; social justice; mandatory quota; gender diversity; non-executive directors; executive directors; quota legacy; female directorship; India